2012
DOI: 10.2967/jnumed.111.097550
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Arterial 18F-FDG Uptake by Fusion of PET and Coronary CT Angiography at Sites of Percutaneous Stenting for Acute Myocardial Infarction and Stable Coronary Artery Disease

Abstract: Whether 18 F-FDG PET can detect inflammation in the coronary arteries remains controversial. We examined 18 F-FDG uptake at the culprit sites of acute myocardial infarction (AMI) after percutaneous coronary stenting (PCS) by coregistering PET and coronary CT angiography (CTA). Methods: Twenty nondiabetic patients with AMI (median age, 62 y; 16 men and 4 women) and 7 nondiabetic patients with stable coronary artery disease (CAD; median age, 67 y; 4 men and 3 women) underwent 18 F-FDG PET and coronary CTA 1-6 d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 29 publications
4
60
0
1
Order By: Relevance
“…The feasibility of using 18 F-FDG for coronary plaque imaging was initially described by Rogers et al (11). We subsequently reported that 12 of 20 patients with recent acute coronary syndromes had increased 18 F-FDG uptake in stented culprit coronary lesions-with a target-to-background ratio greater than 2.0-compared with 1 of 7 in patients with stable coronary artery disease (12). A limitation of coronary imaging with 18 F-FDG is that its uptake by the myocardium frequently cannot be suppressed, despite a high-fat and low-carbohydrate diet (12).…”
Section: F-fdg: Imaging Inflammation With a Ubiquitous Metabolic Subsmentioning
confidence: 99%
“…The feasibility of using 18 F-FDG for coronary plaque imaging was initially described by Rogers et al (11). We subsequently reported that 12 of 20 patients with recent acute coronary syndromes had increased 18 F-FDG uptake in stented culprit coronary lesions-with a target-to-background ratio greater than 2.0-compared with 1 of 7 in patients with stable coronary artery disease (12). A limitation of coronary imaging with 18 F-FDG is that its uptake by the myocardium frequently cannot be suppressed, despite a high-fat and low-carbohydrate diet (12).…”
Section: F-fdg: Imaging Inflammation With a Ubiquitous Metabolic Subsmentioning
confidence: 99%
“…In the case of coronary 18 F-FDG imaging, an additional complication is presented by myocardial activity, which may overlap with plaque activity due to arterial/myocardial motion. 20 Heart motion could be one reason why 18 F-FDG studies investigating coronary plaques have not been strongly conclusive. 18 To partially mitigate blurring due to cardiac motion during Figure 1.…”
Section: Coronary Pet Imagingmentioning
confidence: 99%
“…18,19 In coronary plaque imaging, PET activity originating from very small moving volumes of non-calcified plaques (perhaps as small as a few cubic mm) needs to be quantified with respect to standard uptake value and target-to-background ratio. These measurements will be severely affected by motion of the arteries, effectively reducing both quantified values.…”
Section: Coronary Pet Imagingmentioning
confidence: 99%
“…30 However, these measures have proved only modestly effective, with background myocardial 18F-FDG activity remaining a significant problem in almost half of patients. 29,30 We believe that this lack of specificity is likely to limit the use of 18F-FDG as a biomarker of coronary artery disease risk and that more macrophage specific tracers are required. The novel radio-ligand 11C-PK11195 holds promise in this regard, targeting a translocator protein specific to human macrophages and demonstrating increased uptake in atherosclerotic plaques that correlates with macrophage infiltration.…”
mentioning
confidence: 99%
“…Initial studies were encouraging, with 18F-FDG activity in the proximal vessels and adjacent aorta demonstrating increased activity in patients following acute coronary syndromes compared with those with stable angina. 28,29 However, attempts to examine the coronary vasculature in more detail have been limited by the glycolytic activity of the myocardium, which uses glucose as its predominant energy source and therefore avidly takes up 18F-FDG obscuring any signal in adjacent structures. High-fat, low-carbohydrate diets have been used in an attempt to switch myocardial metabolism to free fatty acid and reduce ventricular uptake.…”
mentioning
confidence: 99%